2022
DOI: 10.7759/cureus.26671
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an auto-immune disease of a relapsing-remitting nature that can cause multiorgan damage depending on several factors, mainly the disease activity. Young age women are the most likely to be affected by the disease and the female-to-male prevalence ratio is approximately 1:10. As the number of SLE patients has been increasing in the last few decades, the annual number of deaths due to the disease and its complications has increased as well, and one of the most important syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 72 publications
0
24
0
7
Order By: Relevance
“…Approximately half of SLE patients will experience cardiac complications [3,4]. Pericarditis, myocarditis, valve disorders, thrombosis, and conduction system abnormalities are among the most prevalent cardiac complications in SLE patients [2]. The most prevalent cardiac manifestation of SLE is pericarditis, which has been linked to poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately half of SLE patients will experience cardiac complications [3,4]. Pericarditis, myocarditis, valve disorders, thrombosis, and conduction system abnormalities are among the most prevalent cardiac complications in SLE patients [2]. The most prevalent cardiac manifestation of SLE is pericarditis, which has been linked to poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…About 25% of all SLE patients develop symptomatic pericarditis at some point throughout the disease, most commonly in conjunction with concomitant pleuritis [7]. Nonetheless, autopsy investigations indicate a higher incidence of subclinical pericarditis [2,8]. Imaging examinations revealed that more than 30% of patients were found to have pericardial involvement [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypotension, pulsus paradoxus, dyspnea, orthopnea, and chest discomfort are typical symptoms and indicators (Figure 1). SLE may be difficult to diagnose, and there is no one clinical symptom or laboratory abnormalities that can definitively rule out the disease [5]. SLE is instead identified based on a combination of symptoms, signs, and relevant laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike T2DM, SLE patients are at an even greater risk of adverse clinical events, as these patients not only might be affected by traditional (Framingham) CVD risk factors, but also afflicted by SLE-disease-specific elements 6 . These SLE-specific risk elements increase the risk of CAD by up to 10 times when compared with the general population and these manifestations are mainly seen among young SLE patients 7,8 …”
mentioning
confidence: 99%